Crisis and Dollarization in Ecuador : Stability, Growth, and Social Equity - Beckerman, Paul; Solimano, Andres (Washington, DC: World Bank, 2013)
Early in 2000, Ecuador, confronted with a serious economic crisis, adopted the US dollar as its national currency, This book examines the conditions that led to this action, describing the repeated cycles of crisis and failed stabilization that fatally undermined confidence in the Ecuadorian sucre. The book then analyzes dollarization's initial results and its effects on inflation, growth, poverty, inequality, marginalization, gender, and the Ecuadoran family. It also puts the Ecuadoran experience with dollarization in an international perspective.